2019
DOI: 10.21608/ejh.2019.6454.1047
|View full text |Cite
|
Sign up to set email alerts
|

The potential protective role of flaxseed extract on ventral prostate in a rat model of streptozotocin-induced diabetes: A histological and immunohistochemical study

Abstract: Background: Diabetes mellitus is a chronic disorder that can affect the reproductive system leading to fertility dysfunction. The prostate plays an important role in the reproduction and it is a frequent target for diabetic complications. Flaxseed is a promising alternative in many chronic diseases due to its health benefits. It has a proposed role in controlling diabetes due to its wide pharmacological activities. Aim: Evaluation of the possible protective role of flaxseed extract on the ventral prostate glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26] Group 3: were orally administered with the aqueous extract of flaxseeds at a dose of 400 mg/kg per day according to previous studies which found that the dose of 400 mg/kg was more effective. [27][28][29] Group 4: were administered with MSG at a dose of 14 mg/kg body weight after 4 hours of treatment with the aqueous extract of flaxseeds, orally at a dose of 400 mg/kg per day. All treatment were carried out for 30 days.…”
Section: Experimental Animals Ethical Permission Was Granted By the Research And Experimentalmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Group 3: were orally administered with the aqueous extract of flaxseeds at a dose of 400 mg/kg per day according to previous studies which found that the dose of 400 mg/kg was more effective. [27][28][29] Group 4: were administered with MSG at a dose of 14 mg/kg body weight after 4 hours of treatment with the aqueous extract of flaxseeds, orally at a dose of 400 mg/kg per day. All treatment were carried out for 30 days.…”
Section: Experimental Animals Ethical Permission Was Granted By the Research And Experimentalmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Group 3: were orally administered with the aqueous extract of flaxseeds at a dose of 400 mg/kg per day according to previous studies which found that the dose of 400 mg/kg was more effective. [27][28][29] Group 4: were administered with MSG at a dose of 14 mg/kg body weight after 4 hours of treatment with the aqueous extract of flaxseeds, orally at a dose of 400 mg/kg per day. All treatment were carried out for 30 days.…”
Section: Experimental Animals Ethical Permission Was Granted By the Research And Experimentalmentioning
confidence: 99%